Empirical analysis between human capital and economic growth in Malaysia from 1975 to 2009: an ARDL approach / Nurul Wahilah Abdul Latif, Nora Yusma Mohamed Yusof and Tan Kwe Lu - Abdul Latif, Nurul Wahilah; Mohamed Yusof, Nora Yusma; Lu, Tan Kwe (2011)
The main purpose of this research is to examine the short run and long run relationships between human capital and economic growth in Malaysia. This paper applies the co-integration and error correction model (ECM) to explore the short run and long run relationships between education variables and economic growth for Malaysia during 1975 to 2009 period. This paper focuses on human capital as one of the determinants of economic growth in Malaysia. Both economics theory and prior research suggest that investment in both human and physical capital can be expected to enhance economic growth. We use data on education variables as a measure of improvements in the level of human capital. The central question is whether human capital in the form of education attainment is related to economic growth. To achieve this objective, the study employs the autoregressive distributed lag model (ARDL) to examine the long run and short run relationships between the educational variables and economic growth in Malaysia. Our result suggests that there exists a co-integrating relationship between education variables and the economic growth.